PENGARUH PENINGKATAN PENJUALAN BERSIH TERHADAP PENINGKATAN LABA OPERASI PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ela Widasari; Evi Yanti (The Asia Pacific Journal Of Management Studies, 2015)
This study aims to determine the effect of increasing net sales on the increase in operating profit in Food and Beverages companies listed on the Indonesia Stock Exchange. With the independent variable as an increase in net sales and the dependent variable as an increase in operating profit.From the calculation results with the help of SPSS V.20, the results of the presentation of the hypothesis with the t test found an increase in net sales has a significant positive effect on the increase in operating profit in Food and Beverages companies listed on the Indonesia Stock Exchange. The results of the t test using 2 parties with t count 3.258 while the t table is 2.042, so that the count> t table (3.258> 2.042). With the results of statistical calculations it is known that R = 0.488 and R square = 0.238. R square can be called the coefficient of determination, in this case it can be concluded that the increase in net sales has a positive effect on the increase in operating profit by 0.238 or 23.8%.